An Eco feminist Reading of Ngugi wa Thiong’o’s Petals of Blood - Obaid Al-Harbi, Aisha (Gezira Journal of Educational Sciences and Humanities; مجلد 12 عدد 1 (2015), 2018)
The aim of this study is to attempt a reading of Thiong’o’s Petals of Blood (1977) from an ecofeminist point of view. Thiong’o’s concern with feminist issues as reflected in his fictional writings is given an ample examination. Yet, very little study is pursued about the ecofeminist tendency in his creative works. Thus, this paper is motivated by the interest to fill in the gap what previous studies have not yet accomplished. The treatment of Petals of Blood from an ecofeminist lens will broaden the analytical perspective and help to gain more comprehensive understanding of the novel. This interdisciplinary approach of relating literature to other fields of knowledge such as feminism and ecology will develop a cultural consciousness of woman's oppression in society and an environmental awareness of the dangers that might negatively affect our planet. The thematic and stylistic analyses of the novel show the destructive impact of colonialism, post-colonialism and patriarchy on the African woman and environment. This study emphasizes the African woman’s potentialities to protect and inhale the environment. For Thiong’o, it is through the incorporation of all the oppressed such as women, peasants, land and animals, environmental sustainability and balance can be attained.